Development of a novel PAN/silazane hybrid polymer for processing of carbon-based fibers with intrinsic oxidation resistance up to 800 C° - Ribeiro, Luiz Fernando Belchior (2017)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência e Engenharia dos Materiais, Florianópolis, 2017.